The Encyclopedia of Juvenile Delinquency and Justice 2017
DOI: 10.1002/9781118524275.ejdj0146
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Juvenile Offenders

Abstract: Within the past decade, reliance on the juvenile justice system to meet the needs of juvenile offenders with mental health concerns has increased. Due to this tendency, research has been conducted on the effectiveness of various intervention and treatment programs/approaches with varied success. Recent literature suggests that because of interrelated problems involved for youth in the juvenile justice system with mental health issues, a dynamic system of care that extends beyond mere treatment within the juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Two of the most significant and recurring findings in the criminal behavior literature are that juvenile (Abram et al, 2003, 2004, 2015; Colins et al, 2010; Fazel et al, 2008; Gottfried & Christopher, 2017; McClelland et al, 2004; Ryan & Redding, 2004; Teplin et al, 2002; Teplin et al, 2012) and adult (Bronson et al, 2017; National Center on Addiction and Substance Abuse at Columbia University, 2010) offenders have high rates of substance use disorders and other psychiatric disorders and experience adverse childhood experiences (ACEs; e.g., sexual, physical abuse) (Aebi et al, 2015; Friestad et al, 2014; King et al, 2011; National Center on Addiction and Substance Abuse at Columbia University, 2010) disproportionately in relation to the general population. Furthermore, ACEs have been linked to substance use and psychiatric disorders (Li et al, 2016; Lindert et al, 2014; Maniglio, 2012; Varese et al, 2012) and these findings generalize across juvenile offenders (Baglivio et al, 2014; Fox et al, 2015; King et al, 2011; Underwood & Washington, 2016; Vahl et al, 2016), adult offenders (Friestad et al, 2014; Kim et al, 2016; Varese et al, 2012), psychiatric patients (Westermair et al, 2018), and general population samples (Björkenstam et al, 2017; McLaughlin et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Two of the most significant and recurring findings in the criminal behavior literature are that juvenile (Abram et al, 2003, 2004, 2015; Colins et al, 2010; Fazel et al, 2008; Gottfried & Christopher, 2017; McClelland et al, 2004; Ryan & Redding, 2004; Teplin et al, 2002; Teplin et al, 2012) and adult (Bronson et al, 2017; National Center on Addiction and Substance Abuse at Columbia University, 2010) offenders have high rates of substance use disorders and other psychiatric disorders and experience adverse childhood experiences (ACEs; e.g., sexual, physical abuse) (Aebi et al, 2015; Friestad et al, 2014; King et al, 2011; National Center on Addiction and Substance Abuse at Columbia University, 2010) disproportionately in relation to the general population. Furthermore, ACEs have been linked to substance use and psychiatric disorders (Li et al, 2016; Lindert et al, 2014; Maniglio, 2012; Varese et al, 2012) and these findings generalize across juvenile offenders (Baglivio et al, 2014; Fox et al, 2015; King et al, 2011; Underwood & Washington, 2016; Vahl et al, 2016), adult offenders (Friestad et al, 2014; Kim et al, 2016; Varese et al, 2012), psychiatric patients (Westermair et al, 2018), and general population samples (Björkenstam et al, 2017; McLaughlin et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, research has begun to examine the role of psychological distress among youth involved within the juvenile justice system. As there is consistently high prevalence of mental illness and psychological distress among youth involved in the juvenile justice system (Archer et al, 2010; Burke et al, 2015; Golzari et al, 2006; Hunsicker, 2007; Kazdin, 2000; Lyu et al, 2015; Underwood & Washington, 2016), it is imperative to understand what factors influence the relationship between psychological distress and early childhood behavioral problems. By identifying risk factors, practitioners and policy makers will be able to adequately address the risk factors for psychological distress and potentially prevent future youth offending.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a significant number of youth in the juvenile justice system experience psychological distress. It is estimated that about 50% to 75% of youth within the juvenile justice system meet the criteria for a mental health disorder (Underwood & Washington, 2016). About 60% of males and two-thirds of females detained in the juvenile justice system meet criteria for one or more psychiatric disorders (Teplin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among incarcerated youth, the most common mental health disorders include affect disorders (i.e., depression), anxiety, conduct disorder, bipolar disorder, ADHD, and PTSD (Underwood & Washington, 2016). Researchers found that 93% of youth with PTSD also had another comorbid psychiatric disorder (Abram et al, 2007).…”
mentioning
confidence: 99%